Effect of supplemental light, pinching, and number of plants per pot on the growth and flowering of chrysanthemum plant (Dendranthema grandiflora Tzvelev) - Jihad Y. Hasan; Ban G. Khushaba; Yousif H. Hammo (Kufa Journal for Agricultural Sciences)
This study was conducted in the plastic house - Nursery of the Duhok University - Duhok governorate-Kurdistan region-Iraq from the period 10th Apr. 2021 to 10th Jan. 2022. This study aimed to investigate the effect of supplemental light (light and without light), pinching (pinching and without pinching) and number of plants per pot (2, 3, and 4) plants/pot on the growth and flowering of chrysanthemum (Dendranthema grandiflora Tzvelev) plant. The results showed that supplemental light for one month delayed the flower bud emergence (223.08) days, and flower anthesis (241.58) days compared with the control (without supplemental light) that gave (198.83, 218.44) days for the two characteristics respectively. Further, supplemental light gave the best results for flower length, flower diameter, flower number, and vase life compared to (without supplemental light). Pinching delayed the flower bud emergence and decreased the plant high, growth index, flower diameter, and vase life of cut flower significantly while it significantly increased the flower diameter and vasa life. Increasing the number of plants per pot to 4 plants caused a significant increment in flower number (8.25) compared with 2 plants which gave 5.64 plants/pot. The triple interaction showed significant differences in all characteristics and number of days to flower bud emergence and flower anthesis were the highest mean for the supplemental light with or without the pinch and 2 plants/pot. Also, the best plant height (72.33) cm and growth index (26761) cm3 were recorded without supplemental light, without pinch with 2 plants/pot. However, the maximum vase life of 26.33 days was found from the interaction of supplemental light, pinch, and 2 plants/pot.